The Effect of Strategic Leadership and Environmental Management on Firm Performance Mediated by Competitive Advantage in The Mining Industry - Nurcahyo, Adrian (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study aims to investigate and analyze the impact of strategic leadership and environmental management on competitive advantage, and the effect of strategic leadership and environmental management on firm performance mediated by competitive advantage within the mining industry in Indonesia. Data for this research were collected from a population of 90 respondents who work in the mining sector and possess a Mining Business License (IUP) as well as are members of the Indonesia Mining Association (IMA). The sample includes business owners, mining contractors, mining consultants, traders, and beneficiation plant operators. This study analyzed the effects of Strategic Leadership and Environmental Management on Competitive Advantage and Firm Performance in the mining industry using Structural Equation Modeling (SEM) with Partial Least Squares (PLS). The findings reveal that Strategic Leadership and Environmental Management significantly enhance Competitive Advantage. However, their direct effects on Firm Performance are not significant, suggesting their impact is mediated through Competitive Advantage. Notably, Competitive Advantage strongly drives Firm Performance. These results highlight the critical roles of strategic leadership and sustainable practices in fostering competitive strengths, ultimately leading to superior performance outcomes. Mining companies should focus on these areas to achieve and sustain competitive advantages. Future research should explore additional mediating factors and examine these relationships in various contexts to deepen the understanding of these dynamics within the mining sector.